Temperature Data in 3d Structure Reveal the Internal COD Involvement in Molecular Form (Global Journal of Science Frontier Research, 2020)
Addition of small molecule into force is going to be the task of another rule based activation for any meaningful application in biology of animalia kingdom of existence. Otherwise it is mandatory to fulfill the norms for adequacy principle arising out of carbon value in force here in protein or other where carbon alone dominates the due course of action and all. Accordingly we have developed an internal one proposal for any meaningful application in carbon based study of intervening elements of interaction arising from carbon value. Additional to existing calculations in modeling, it is going to be the one only force will dominate the scenario of molecular alteration for many salvations in living organisms. According to rule of law coming from carbon profile, the hydrogen atom also to be the main part of the value calculation and all. According to new force of carbon calculation, it is here calculated to be the internal one of carbon profile found in 3D structure where another part of intervening elements taken into account.
Keywords: ICOD; temperature factor; carbon value; protein; DNA/RNA; CARd3D; cohesive force; rule of law